Detection of Recurrent Prostate Cancer With 18F-Fluciclovine PET/MRI - Selnæs, Kirsten Margrete; Krüger-Stokke, Brage; Elschot, Mattijs; Johansen, Håkon; Steen, Per Arvid; Langørgen, Sverre; Aksnessæther, Bjørg Yksnøy; Indrebø, Gunnar; Sjøbakk, Torill Anita Eidhammer; Tessem, May-Britt; Moestue, Siver Andreas; Knobel, Heidi; et al. (Frontiers in Oncology, 2020)
Objective: Simultaneous PET/MRI combines soft-tissue contrast of MRI with high molecular sensitivity of PET in one session. The aim of this prospective study was to evaluate detection rates of recurrent prostate cancer by 18F-fluciclovine PET/MRI. Methods: Patients with biochemical recurrence or persistently detectable prostate specific antigen (PSA), were examined with simultaneous 18F-fluciclovine PET/MRI. Multiparametric MRI (mpMRI) and PET/MRI were scored on a 3-point scale (1-negative, 2-equivocal, 3-recurrence/metastasis) and detection rates (number of patients with suspicious findings divided by total number of patients) were reported. Detection rates were further stratified based on PSA level, PSA doubling time (PSAdt), and primary treatment. Results: Among patients eligible for analysis (n=84), 54 lesions were detected in 38 patients by either mpMRI or PET/MRI. Detection rates were 41.7% for mpMRI and 39.3% for PET/MRI (score 2 and 3 considered positive). There were no significant differences in detection rates for mpMRI versus PET/MRI. Disease detection rates were higher in patients with PSA≥1ng/mL than in patients with lower PSA levels but did not differ between patients with PSAdt above versus below 6 months. Detection rates in patients with primary radiation therapy were higher than in patients with primary surgery. Conclusion: Combined 18F-fluciclovine PET/MRI can detect lesions suspicious for recurrent prostate cancer in patients with a range of PSA levels. Combined PET/MRI may be useful to select patients for appropriate treatment, but is of limited use at low PSA values, and the clinical value of 18F-fluciclovine PET/MRI in this study was too low to justify routine clinical use.